THE ROLE OF THE INDONESIAN EMBASSY IN HANDLING CASES OF SEXUAL VIOLENCE AGAINST FEMALE PMI IN MALAYSIA IN 2014-2019 - Magdalena, Anastasya Alcita (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Indonesian Migrant Workers or abbreviated as PMI are workers from Indonesia who work abroad. Malaysia as the main destination country for PMIs has more access to employ workers from Indonesia. The large number of PMIs in Malaysia also causes a high level of violence that occurs in Malaysia, especially cases of sexual violence against female PMIs in Malaysia. This is being a particular concern to efforts to protect PMI's human security through protective diplomacy carried out by the Indonesian Embassy in Malaysia. The research method used is reviewing data from the official website. It was found that the Indonesian Embassy was supervising cases of sexual violence against female PMIs in Malaysia by making protection diplomatic efforts with related parties to uphold the human security of female PMIs in Malaysia. Keywords: human security, Indonesian Embassy, PMI, protection diplomatic